National technology and industrial base integration : how to overcome barriers and capitalize on cooperation /: how to overcome barriers and capitalize on cooperation. (2018) - McCormick, Rhys; Cohen, Samantha; Hunter, Andrew P; Sanders, Gregory; Mooney, Samuel; Herschlag, Daniel
No abstract available